2022
DOI: 10.1186/s40168-022-01290-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil-derived bacteria endow Camellia weevil with more ability to resist plant chemical defense

Abstract: Background Herbivorous insects acquire their gut microbiota from diverse sources, and these microorganisms play significant roles in insect hosts’ tolerance to plant secondary defensive compounds. Camellia weevil (Curculio chinensis) (CW) is an obligate seed parasite of Camellia oleifera plants. Our previous study linked the CW’s gut microbiome to the tolerance of the tea saponin (TS) in C. oleifera seeds. However, the source of these gut microbiomes, the key bacteria involved in TS tolerance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Similar results demonstrating the importance of stochastic processes were also observed in studies on gut microbial communities in Drosophila simulans and Dicranocephalus wallichii bowringi [ 39 ]. Another study also showed that Curculio chinensis gut microbiome was derived from the surrounding environmental microbiome and was more affected by the microbiome from soil than that from fruits [ 40 ]. However, our results demonstrated that both factors contribute to gut microbiome community assembly, which would perhaps be more conducive to S. noctilio spreading colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results demonstrating the importance of stochastic processes were also observed in studies on gut microbial communities in Drosophila simulans and Dicranocephalus wallichii bowringi [ 39 ]. Another study also showed that Curculio chinensis gut microbiome was derived from the surrounding environmental microbiome and was more affected by the microbiome from soil than that from fruits [ 40 ]. However, our results demonstrated that both factors contribute to gut microbiome community assembly, which would perhaps be more conducive to S. noctilio spreading colonization.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that higher tiers of endosymbionts (i.e., Wolbachia , Sodalis, and Rickettsia ) were present in weevils at localities with higher temperatures; lower numbers of Wolbachia and Rickettsia were detected in a population found in regions with higher snowfall. Furthermore, microorganisms acquired from the surrounding environment can enhance the fitness of insect hosts ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tea saponin (TS) of Camellia oleifera is triterpenoids that is toxic to seed-feeding weevil pest, Curculio chinensis (CW) ( 2 , 20 , 21 ). The TS content in different insect-resistant C. oleifera clones was negatively correlated with the damage level of CW ( 2 , 20 , 21 ). Studies have shown that over 220 insect species can feed on C. oleifera , and only CW is specialized seed feeder ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Acinetobacter sp. AS23 strain was the dominant strain in the gut microbiome of the surviving larvae with high resistance to host plants, and the abundance of AS23 strain was positively correlated with the TS content of host plants ( 21 ). Traceability analysis showed that the probability of the bacteria coming from soil was as high as 96% ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation